Apatite‐Binding Nanoparticulate Agonist of Hedgehog Signaling for Bone Repair. (5th February 2020) - Zhang, Xiao; Fan, Jiabing; Lee, Chung‐Sung; Kim, Soyon; Chen, Chen; Aghaloo, Tara; Lee, Min
Abstract: The hedgehog signaling pathway plays a critical role in bone development and regeneration. Applications of hedgehog morphogens or small molecular agonists are of interest in bone repair but constrained by low stability, high dose requirement, and nonspecific targeting in vivo. Herein, a nanoparticulate agonist as a new type of hedgehog signaling activator is developed for efficacious bone healing. The shell of nanoparticulate agonist consists of palmitic acid and oxysterol, which could modify hedgehog function and bind with the smoothened receptor to positively modulate hedgehog signaling. Meanwhile, the core is assembled with the sonic hedgehog gene/polyethyleneimine complex, which could synergistically enhance hedgehog signaling with oxysterol constituents. Moreover, alendronate is introduced into the nanoparticulate agonist to bind with hydroxyapatite for potential bone tissue targeting. Lastly, the nanoparticulate agonist surface is decorated with the guanidine group to overcome cell membrane barriers. The created multifunctional nanoparticulate agonist is successfully integrated onto apatite‐coated 3D scaffolds and demonstrates greatly improved osteogenesis in vitro and calvarial bone healing. This work suggests a novel biomaterial design to specifically promote hedgehog signaling for the treatment of bone defects. Abstract : Multifunctional nanoparticulate agonists (MNAs) are developed for activating the hedgehog signaling pathway and inducing bone tissue regeneration. These MNAs are assembled from 20(S)‐hydroxycholesterol and palmitic acid in aqueous solutions. The MNAs demonstrate strong osteoinductive properties by regulating hedgehog signaling. When combined with apatite‐coated scaffolds, the MNAs promote efficacious bone healing in a mouse non‐healing calvarial defect.